Buddhist Principles for Development of Human Behavior, Morality, Mind and Wisdom - Ruksat, Suvin; Channuwong, Sukhumpong; Changcharoen, Chompoonuch; (Sairung Daengngam), Phraratchawinaiwachiramethi; Khethong, Phramaha Khanob (Journal of Posthumanism, 2025)
This research article aims to study the Buddhist principles for development of human behavior, morality, mind and wisdom. Qualitive method with documentary study was applied in this research. The results of the study were found that human behavior is influenced by internal factors such as the inherent mental state and temperament. Besides, there are external factors including upbringing, associations with friends, and the surrounding environment. The development of morality in Buddhist means, at least observing and following the five precepts namely: to refrain from killing, to refrain from stealing, to refrain from committing adultery or sexual misconduct, to refrain from false speech and to refrain from taking intoxicants that cause heedlessness. Buddhism teaches the development of precepts to purify the body and speech from sins and unwholesome actions. Mind is very important as humans think, plan, and intend before doing something. Mind is a leader of all behavioral movement and activity. If the mind is purified and peaceful, one will experience happiness and bliss in their lives. Buddhism encourages humans to develop wisdom through tranquil and insightful meditation. With a tranquil mind, people can see the truth of all things, be calm and reasonable. Calmness, happiness, and stability of mind can be achieved through meditation practice. Buddhism teaches people to cultivate their wisdom at all the time. Wisdom can be achieved through learning, critical thinking and meditation. Following the Buddhist principles result in proper and virtuous behavior, actions, and expressions, and eventually leads to happiness and peace of mind.